Antixenosis resistance in okra accessions against shoot and fruit borer Earias vittella (Fab.) - N. Karthika, Anitha. S, (Journal of Phytology, 2018)
The present study is to analyse the antixenosis mechanisms of resistance in ten okra accessions against Shoot and Fruit borer E. vittella. With regard to the free choice feeding preference, the accessions IC140880 and Trichi local were not preferred by any larvae even up to 8 h. The fruit damage of Coimbatore local by the larvae in 8 hours was recorded as lowest, in confined condition. The accession IC 282228 fruit was bored up to a length 9.1 cm by the larvae in 8 h. On studying the oviposition preference, the accessions IC140880 and Trichi local were least preferred by E. vittella adults. The length and breadth and number of trichomes of these accessions were recorded as maximum. It was observed that the fruit length of IC140880 were greater than other accessions whereas Trichi local recorded higher fruit width compared to other accessions. While assessing the Fruit angle to stem, Coimbatore local recorded a higher value followed by Trichi local, IC140880 and IC 218877. The incidence of shoot and fruit borer was high in IC282228. In overall observation, weight and yield of the fruit is high in IC140880 followed by Trichi local.